2020
DOI: 10.1128/jvi.01883-19
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibody Induction by HIV-1 Envelope Glycoprotein SOSIP Trimers on Iron Oxide Nanoparticles May Be Impaired by Mannose Binding Lectin

Abstract: We covalently attached human immunodeficiency virus type 1 (HIV-1) Env SOSIP trimers to iron oxide nanoparticles (IO-NPs) to create a particulate immunogen for neutralizing antibody (NAb) induction. The attached trimers, ∼20 per particle, retained native-like antigenicity, judged by reactivity with NAbs and non-NAbs. Bivalent (BG505 and B41) trimer IO-NPs were made, as were IO-NPs displaying B41 trimers carrying a PADRE T-cell helper epitope (TCHE). We immunized mice with B41 soluble or IO-NP trimers after PAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 108 publications
1
44
1
Order By: Relevance
“…Also in agreement with our observations, Pejawar-Gaddy et al have reported that the inclusion of DOTAP to double-functionalised, DOPC-based interbilayer-cross-linked multilamellar vesicles (ICMVs) improved the conjugation efficiency of Env trimers from around 5% to slightly above 20% [ 17 ]. In stark contrast to our findings, Ringe et al showed that Env trimers can be coupled to the surface of negatively charged nanoparticles using EDC/Sulfo-NHS chemistry [ 32 ]. The relatively high Env trimer:nanoparticle ratio and high Env trimer bulk concentration may have contributed to the higher number of displayed Env trimers.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Also in agreement with our observations, Pejawar-Gaddy et al have reported that the inclusion of DOTAP to double-functionalised, DOPC-based interbilayer-cross-linked multilamellar vesicles (ICMVs) improved the conjugation efficiency of Env trimers from around 5% to slightly above 20% [ 17 ]. In stark contrast to our findings, Ringe et al showed that Env trimers can be coupled to the surface of negatively charged nanoparticles using EDC/Sulfo-NHS chemistry [ 32 ]. The relatively high Env trimer:nanoparticle ratio and high Env trimer bulk concentration may have contributed to the higher number of displayed Env trimers.…”
Section: Resultscontrasting
confidence: 99%
“…With regard to the oriented display, homology models and calculations/estimations of the degree of deprotonation of the Env trimer’s primary amines, suggest that not all primary amines are equally accessible and nucleophilic/reactive (unpublished observations). In concordance with this, recently published homology models of two SOSIP trimers indicate that most lysine residues at the apex of the Env trimer are shielded by glycans [ 32 ]. However, many lysine residues on the glycan-free base appear accessible.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…While previous studies of nanoparticle-displayed HIV-1 Env trimers have demonstrated enhanced immunogenicity39 , the effects are often modest compared to those observed for other antigens1,2,18,36 . While there may exist intrinsic peculiarities to HIV-1 Env that limit increases in Ab responses upon multivalent display40,41 , limitations associated with epitope inaccessibility caused by crowding of the trimers on nanoparticle surfaces have also been identified19 . This observation strongly motivates the exploration of antigen presentation geometry through the custom design of nanoparticle scaffolds to most effectively elicit the desired immune response.…”
mentioning
confidence: 99%